2015
DOI: 10.1371/journal.pgen.1005279
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Changes to a Transcriptional Silencer Element Confers Phenotypic Diversity within and between Drosophila Species

Abstract: The modification of transcriptional regulation has become increasingly appreciated as a major contributor to morphological evolution. However, the role of negative-acting control elements (e.g. silencers) in generating morphological diversity has been generally overlooked relative to positive-acting “enhancer” elements. The highly variable body coloration patterns among Drosophilid insects represents a powerful model system in which the molecular alterations that underlie phenotypic diversity can be defined. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 55 publications
0
53
0
Order By: Relevance
“…Genetic differences in ebony cis -regulatory sequences also appear to contribute to variable abdominal pigmentation in other populations of D. melanogaster and other species (Bastide et al 2013; Johnson et al 2015; Dembeck et al 2015b; Endler et al 2016). For example, an association study using the Drosophila Genetic Reference Panel (DGRP) of D. melanogaster strains isolated from a population in Raleigh, North Carolina (Mackay et al 2012) found a significant correlation between a noncoding variant located within a known cis- regulatory element of ebony and pigmentation variation within this population (Dembeck et al 2015b).…”
Section: Abdominal Pigmentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Genetic differences in ebony cis -regulatory sequences also appear to contribute to variable abdominal pigmentation in other populations of D. melanogaster and other species (Bastide et al 2013; Johnson et al 2015; Dembeck et al 2015b; Endler et al 2016). For example, an association study using the Drosophila Genetic Reference Panel (DGRP) of D. melanogaster strains isolated from a population in Raleigh, North Carolina (Mackay et al 2012) found a significant correlation between a noncoding variant located within a known cis- regulatory element of ebony and pigmentation variation within this population (Dembeck et al 2015b).…”
Section: Abdominal Pigmentationmentioning
confidence: 99%
“…Weak associations with noncoding SNPs in ebony cis -regulatory elements were also observed for European populations of D. melanogaster (Bastide et al 2013; Dembeck et al 2015a; Endler et al 2016), with the most highly ranked SNP associated with ebony in Bastide et al (2013) located in a sequence that inhibits ebony expression in male abdominal segments during development. Outside of D. melanogaster , genetic variation linked to ebony has been shown to be associated with polymorphic abdominal pigmentation within Drosophila americana (Wittkopp et al 2009) and Drosophila auraria (Johnson et al 2015). In this latter species, specific alleles of ebony cis -regulatory sequences were identified in light and dark individuals, and transgenic analyses of reporter genes were used to demonstrate the effects of these variable sites on ebony expression (Johnson et al 2015).…”
Section: Abdominal Pigmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, expression of ftz in Artemia was homeotic-like but so weak as to be almost undetectable (Heffer et al 2010). Alternatively, acquisition of silencers may have led to loss of expression, as seen recently for color patterning genes (Johnson et al 2015). We previously proposed that it was loss- or low-level expression of ftz in embryos that was permissive for gain-of-function changes in its protein function.…”
Section: Gain Of Function Changes In An Embryonic Regulatory Genementioning
confidence: 95%